Students’ Information Literacy at the MTsN 4 Banda Aceh Based on Empowering Eight Model - Yuliana, Cut Putroe; A. Rasyid, Saifuddin; Manan, Abdul; Putra, Rahmad Syah; Parwita, Khairi (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2023)
This article discusses students' information literacy at the MTsN 4 Banda Aceh library using Empowering 8 model. This model uses a problem-solving approach to resource-based learning. Information literacy skills include identifying, and exploring appropriate sources and information on a topic, selecting and recording relevant information, collecting appropriate quotations, organizing, creating, presenting, assessing, and implementing. The purpose of this study is to determine students' information literacy in the library of MTsN 4 Banda Aceh by using the Empowering 8 model. Data collection techniques used are interview, documentation and questionnaires. The results of this study indicate that student's level of information literacy is classified as good. Both include identification, organizational selection, creating literacy, presentation, assessment and aspects of the application of information literacy. However, the most dominant level of student information literacy in the library of MTsN 4 Banda Aceh is in the organizational and assessment aspects, with 62.28% of students saying “yes” and 37.71% saying “no". While the lowest level of information literacy was in the information selection aspect, 26.27% of students said "yes," and 73.73% said "no”. Improving student information literacy competence can be encouraged by establishing centralized policies that must be implemented to form innovations carried out by each school.